Produtividade, componentes de rendimento de grãos e qualidade de genótipos de trigo duplo propósito submetidos ao corte - Santos, Paulino Ricardo Ribeiro dos (2014)
Sustainable development of agriculture is based on the reduction of production costs and adding value, which can be obtained through the use of dual-purpose wheat. The aim of this study was to evaluate the yield and quality of forage components of grain yield and quality industrial flour of dual-purpose genotypes wheat submitted to cut. Assays were performed in the experimental area of the Centre for Development and Diffusion of Technology - . CEDETEC located in Cascavel , Paraná harvests in 2012 and 2013 to assess the handling of cut, as the production of forage, was used in a randomized block design with four replications in yield components and industrial quality of wheat flour the experimental randomized block design with four replications in a split plot layout was used. Each experimental plot consisted of eight genotypes (BARTT-108, BARTT-109, BARTT-111, BARTT-112, BARTT-115, BARTT-116, BARTT-118 and BRS Tarumã) and handling cut the subplot: without cut and a cut. The genotypes of dual purpose wheat were tested for production and forage quality: dry matter in both test acid detergent fiber, neutral detergent fiber, lignin, cellulose, hemicellulose and crude protein in the second test, the components of yield grain were: size of spike, number of spikelet per spike, number of grains per spike, number of spike m-2, as well as the characteristic of plant height, thousand grain weight, hectoliter weight and grain yield ( kg ha-¹) for assessing the quality of wheat flour the color of flour, falling number and alveography was used. The results of production and forage quality in the first test, the results were significant for dry variable, since the variable second test showed no significant difference with the cut. For variables, acid detergent fiber, neutral detergent fiber, lignin, cellulose, hemicellulose, crude protein and no significant difference was observed. Yield components in grain size variables of spike, number of spike m - 2, plant height, thousand grain weight and hectoliter weight all statistically differ as to genotype, cutting only influenced the variables size of spike, number of spike per m-2, plant height, thousand grain weight, hectoliter weight and grain yield. In the second trial the grain yield was not affected by the cut. In both tests the quality of wheat flour genotypes showed significant differences in the variables of color, falling number and alveography, as the genotype, the crop factor did not influence the first test the color a * and b *. Some components of grain yield and quality were influenced by cutting and productivity was higher than the regional average. The flour genotypes BARTT presents desirable characteristics of use for cakes, biscuits, fresh pasta industry and for domestic or mixed with flour of cultivars producing stronger gluten as BRS Tarumã